(untitled) (American Journal of Islam and Society, 2011)
This paper identifies and makes a comparative analysis of issues in Muslim liberalist and contemporary Islamic revivalist thought as seen and discussed by William Montgomery Watt and Yoginder Sikand. They consider Muslim liberalists thought as creative interpretations, which contribute constructively toward the development of Islamic thought; however, they maintain that Islamic revivalists demonstrate rigidity, idealism, and fundamentalism and cause the development of radical thought. In the first part of this article, a number of criticisms that have been raised by Watt and Sikand on behalf of Muslim liberalists against Islamic revivalists are critically analyzed, and the position of Islamic revivalists is clarified. The criticisms deal with the question of change, the worldview, the role of reason, and the stand of both groups with regard to secularism, nationalism, and religious pluralism, and lastly, the issue of politics and the Islamic state. The second part offers the issues that are seen as pertinent by the Islamic revivalists for the development of the Islamic Ummah for humanity. Finally, it is argued that the thought developed by Muslim liberalists is heavily influenced by liberalism and of guidance for civilizational development. Thus, this thought is rightly termed as Islamic revivalist thought.